2015
DOI: 10.1016/j.jpsychires.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine enhances the ability of paliperidone to decrease alcohol drinking

Abstract: Alcohol use disorder commonly occurs in patients with schizophrenia and dramatically worsens their course. The atypical antipsychotic clozapine has been associated with reduced drinking in these patients, but its toxicity reduces its use. We have attempted to create a clozapine-like drug by combining agents that capture components of clozapine’s pharmacologic action, including its weak dopamine D2 blockade and noradrenergic modulation. The current study assessed whether paliperidone, a dopamine D2 receptor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…1 AUD usually occurs in patients with schizophrenia, contributes greatly to their morbidity 2 and drastically increased their course. 3 There are few data available on pharmacological approaches in this population, but among antipsychotics, clozapine shows positive evidence in the literature, 4 it has been associated with a decrease in alcohol consumption in patients with schizophrenia, but its toxicity reduces its use. 3 In addition, this group of patients often show poor adherence to medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 AUD usually occurs in patients with schizophrenia, contributes greatly to their morbidity 2 and drastically increased their course. 3 There are few data available on pharmacological approaches in this population, but among antipsychotics, clozapine shows positive evidence in the literature, 4 it has been associated with a decrease in alcohol consumption in patients with schizophrenia, but its toxicity reduces its use. 3 In addition, this group of patients often show poor adherence to medication.…”
Section: Discussionmentioning
confidence: 99%
“…3 There are few data available on pharmacological approaches in this population, but among antipsychotics, clozapine shows positive evidence in the literature, 4 it has been associated with a decrease in alcohol consumption in patients with schizophrenia, but its toxicity reduces its use. 3 In addition, this group of patients often show poor adherence to medication. To improve substance consumption and adherence to treatment in schizophrenic patients with SUD, direct and indirect evidence tends to favor the use of second generation antipsychotics (SGA), particularly those with less metabolic effects, cardiovascular and extra pyramidal, as well as those with their depot formulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, remoxipride decreases the number of alcohol presentations per session in rats by inducing an early termination of the alcohol-drinking bout during the self-administration session [132] and repeated systemic administration of paliperidone decreased the acquisition of alcohol consumption in high-alcohol-preferring P rats [156]. In addition, a recent study, comparing the effect of the atypical antipsychotic drug clozapine to that of the traditional dopamine D2 receptor antagonist haloperidol, showed that clozapine but not haloperidol attenuated the initiation of alcohol drinking and development of alcohol preference in highalcohol-preferring rats [157].…”
Section: Preclinical Evidence For the Use Of Atypical Dopamine D2 Recmentioning
confidence: 99%
“…We have used the hamster model in previous studies to test the effects of antipsychotic drugs (e.g., risperidone, paliperidone), alone or in combination with a NE reuptake inhibitor, on alcohol drinking (Chau et al, 2015; Gulick et al, 2014; Khokhar et al, 2015). While results from our studies are not in agreement with rat studies assessing the effects of antipsychotics on alcohol withdrawal symptoms (Celikyurt et al, 2011; Uzbay, 2012), possibly due to the lack of demonstrable withdrawal in the hamster (Kulkosky and Cornell, 1979), our findings in the hamster are consistent with reports from human studies (Green et al, 2003; Green et al, 2007), further supporting our use of the hamster model.…”
Section: Introductionmentioning
confidence: 99%